Leveraging the Microbiome for Obesity: Moving From Form to Function - Lee, Anna H.; Manly, Amanda; Dong, Tien S. (Frontiers in Endocrinology, 2022)
Treatment of obesity, an ongoing global epidemic, is challenging, as weight-loss efforts require a multidisciplinary approach addressing both behavioral and biologic needs that are not completely understood. Recent studies of the gut microbiome may provide better insight into the condition, and ultimately serve to advance more effective therapies. Research in this field has shifted from analyzing microbiome compositional differences to investigating functional changes that affect disease pathophysiology and outcome. Bacteria-derived metabolites are a way to bridge compositional changes to functional consequences. Through the production of metabolites, such as short chain fatty acids, tryptophan derivatives and bile acids, and interactions with peripheral and central signaling pathways, the gut microbiome may alter the body’s metabolic and behavioral responses to food. Here, we summarize these mechanisms driven by gut-derived metabolites, through which the microbiome is thought to contribute to obesity, as well as review recent investigations of interventions related to these metabolites. Limitations of existing research, primarily due to paucity of causal studies in humans, are also discussed in this review.